Positive Schooling and Child Development International Perspectives (Springer Singapore, 2018)
This volume discusses the importance of positive schooling in producing responsible and potentially productive adults. Students are generally more motivated to do well and to realize their full potential in schools that have a positive schooling climate, where they feel safe, included and supported. Nevertheless, the reality in today's schools is very different. This volume discusses the major challenges faced by children and adolescents in schools, including problems with curricula, safety issues, lack of inclusive policies, non-availability of teachers, ineffective teaching, insensitivity towards students' issues, improper evaluation methods, harmful disciplinary measures, and so on. Experts in child psychology and education discuss these issues at length in this volume and offer viable solutions for policymakers, school administrators, teachers and parents to make suitable changes and create a positive atmosphere in educational institutions. This volume further discusses the role of various stakeholders---school principals, teachers, counsellors and psychologists---in addressing these challenges. In addition, it raises other, emerging issues which have not been covered in previous volumes on this topic and offers evidence-based suggestions to address them. The intended readership of the volume is researchers and students of psychology, education, sociology, social work and public health, and school teachers, administrators and teacher-trainers. .